Remarks on the type of the Linnaean name Asplenium marinum (Aspleniaceae) - Ferrer-Gallego, P. Pablo (Phytotaxa, 2016)
The typification of the Linnaean name Asplenium marinum (Aspleniaceae) is revised. This name had previously been lectotypified by Reichstein in 1981 from a specimen kept at the herbarium LINN. However, Linnaeus cited a specimen from the Burser herbarium at UPS in the protologue, and therefore in lectotype designation this specimen must be chosen according to Art. 9.12 of the Melbourne Code.